2005
DOI: 10.1073/pnas.0408646102
|View full text |Cite
|
Sign up to set email alerts
|

Conformational changes during the nanosecond-to-millisecond unfolding of ubiquitin

Abstract: Steady-state and transient conformational changes upon the thermal unfolding of ubiquitin were investigated with nonlinear IR spectroscopy of the amide I vibrations. Equilibrium temperaturedependent 2D IR spectroscopy reveals the unfolding of the ␤-sheet of ubiquitin through the loss of cross peaks formed between transitions arising from delocalized vibrations of the ␤-sheet. Transient unfolding after a nanosecond temperature jump is monitored with dispersed vibrational echo spectroscopy, a projection of the 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

22
187
2

Year Published

2005
2005
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(212 citation statements)
references
References 51 publications
22
187
2
Order By: Relevance
“…In a study of thermal unfolding based on IR spectroscopy, Chung et al (37) found that the ␤-strands I and II are more stable than the ␤-strands III and V, which contrasts sharply with our results. It thus appears that the pathways followed in thermal and force-induced unfolding of ubiquitin indeed are different.…”
Section: Summary and Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…In a study of thermal unfolding based on IR spectroscopy, Chung et al (37) found that the ␤-strands I and II are more stable than the ␤-strands III and V, which contrasts sharply with our results. It thus appears that the pathways followed in thermal and force-induced unfolding of ubiquitin indeed are different.…”
Section: Summary and Discussioncontrasting
confidence: 57%
“…The folding and unfolding of ubiquitin at zero force has been studied extensively by using both chemical denaturants (35) and temperature denaturation (36,37), and the flexibility of the native state also has been examined (38). In a study of thermal unfolding based on IR spectroscopy, Chung et al (37) found that the ␤-strands I and II are more stable than the ␤-strands III and V, which contrasts sharply with our results.…”
Section: Summary and Discussioncontrasting
confidence: 56%
“…Recent applications of this method to biologically related molecules have yielded novel structural and dynamical results not readily obtainable by other methods for small peptides (7,8), soluble helices (9, 10), membrane-bound helices (11), lipids (12), ␤-sheets (13,14), and model secondary structures (15,16). The 2D IR approach is one that can be immediately applicable to a wide variety of sample types ranging from solutions to solids, including aqueous and lipid environments.…”
mentioning
confidence: 99%
“…The 2D IR approach proves to be a useful structural method for the study of membrane-bound structures. The 27-residue human erythrocyte protein Glycophorin A transmembrane peptide sequence: KKITLIIFG79VMAGVIGTILLISWG94IKK was labeled at G79 and G94 with 13 tertiary interaction ͉ vibrational spectra ͉ multidimensional spectroscopy T wo-dimensional IR spectroscopy (1-6) is a promising new method with which to probe structures and their motions in complex systems. Recent applications of this method to biologically related molecules have yielded novel structural and dynamical results not readily obtainable by other methods for small peptides (7,8), soluble helices (9, 10), membrane-bound helices (11), lipids (12), ␤-sheets (13, 14), and model secondary structures (15, 16).…”
mentioning
confidence: 99%
“…In this way, a ''movie'' of the molecular motion can be constructed (24). This experimental scheme has recently been realized to study optically triggered ␣-helix formation in a peptide with time-resolved 2D-IR spectroscopy (25) and to study thermally induced unfolding of a protein with dispersed vibrational echo spectroscopy (26). Applying such methods to study the motion of molecular devices, which, in many cases, can also be externally triggered (5,27), will reveal fundamental aspects of their physics and chemistry.…”
mentioning
confidence: 99%